Disability Studies and Spanish Culture : Films, Novels, the Comic and the Public Exhibition. - Fraser, Benjamin. (Representations: Health, Disability, Culture and Society Series, 2013)
Disability Studies and Spanish Culture is the first book to explore representations of intellectual disabilities (Down syndrome, autism, alexia/agnosia) in contemporary Spanish films, novels, a graphic novel/comic and public expositions by disabled artists.